A Case of Severe Neutropenia From Short-Term Exposure to Moxifloxacin. (March 2017) - Chen, Weihan; Van Buren, Peter Noel
Moxifloxacin is commonly prescribed in the inpatient and outpatient management of community-acquired pneumonia and other common infections. We report a case of a 76-year-old man who developed severe neutropenia after several days of treatment for community-acquired pneumonia. The patient had a history of alcohol abuse; however, there were no other offending medications prescribed, and a thorough laboratory workup for other possible causes of neutropenia was negative. The patient's neutrophils and white blood count responded quickly to cessation of fluoroquinolones. This case highlights the importance of identifying patients that might be at high risk for neutropenia that may need closer monitoring on this commonly prescribed medication.